2016
DOI: 10.1186/s13561-016-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional inequalities in child malnutrition in Egypt, Jordan, and Yemen: a Blinder-Oaxaca decomposition analysis

Abstract: There is substantial evidence that on average, urban children have better health outcomes than rural children. This paper investigates the underlying factors that account for the regional disparities in child malnutrition in three Arab countries, namely; Egypt, Jordan, and Yemen. We use data on a nationally representative sample from the most recent rounds of the Demographic and Health Survey. A Blinder-Oaxaca decomposition analysis is conducted to decompose the rural-urban differences in child nutrition outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 22 publications
7
35
0
Order By: Relevance
“…In the last step of our analysis, we applied a regression‐decomposition to assess the ability of the various determinants described above to predict spatial patterns in stunting and differences between very high‐burden and low‐burden districts. This approach has been used widely in literature to study mean outcome differences between groups (Jann, ), including differences in child malnutrition between geographical areas (Sharaf & Rashad, ; Spears et al, ; Srinivasan et al, ) and between populations measured at different points of time (Headey, Hoddinott, Ali, Tesfaye, & Dereje, ). This analysis effectively combines the analysis of differences in means of the explanatory variables ( X ) and regression estimates of the coefficients associated with these variables (β X ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last step of our analysis, we applied a regression‐decomposition to assess the ability of the various determinants described above to predict spatial patterns in stunting and differences between very high‐burden and low‐burden districts. This approach has been used widely in literature to study mean outcome differences between groups (Jann, ), including differences in child malnutrition between geographical areas (Sharaf & Rashad, ; Spears et al, ; Srinivasan et al, ) and between populations measured at different points of time (Headey, Hoddinott, Ali, Tesfaye, & Dereje, ). This analysis effectively combines the analysis of differences in means of the explanatory variables ( X ) and regression estimates of the coefficients associated with these variables (β X ).…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies have shown that child undernutrition clusters in specific regions in developing countries (Fenn, Morris, & Frost, 2004;Gebreyesus, Mariam, Woldehanna, & Lindtjorn, 2016) and different types of spatial analysis studies have been conducted to identify geographical inequalities in child stunting (Fenn et al, 2004, Gebreyesus et al, 2016, Adekanmbi, Uthman, & Mudasiru, 2013, Alemu, Ahmed, Yalew, & Birhanu, 2016. However, much less has been done on explaining the factors that contribute to spatial variability in stunting (Di Cesare et al, 2015;Haile, Azage, Mola, & Rainey, 2016;Sharaf & Rashad, 2016;Srinivasan, Zanello, & Shankar, 2013), particularly in India. Although India is a highly populated country with a high burden of stunting, limited evidence exists on spatial analysis to examine the patterns of stunting across the country.…”
mentioning
confidence: 99%
“…In contrast, if a determinant has either a small regression coefficient or small change over time, the decomposition analysis will not identify the determinant as an important driver of anaemia reduction. Regression-decomposition has been used widely to study mean outcome differences between groups, 33 including differences in child malnutrition between geographical areas 34–36 and between populations measured at different points of time. 37 Because changes in Hb and anaemia were minimal for non-pregnant women, the decomposition analyses were conducted only for children and pregnant women.…”
Section: Methodsmentioning
confidence: 99%
“…41,42 SES and rural-urban inequalities in underweight were observed in our study and also have been highlighted by many studies. [43][44][45] Inequality of income between rural and urban households explains most of the malnutrition gap. 44 Understanding of the nature and the underlying factors behind urban-rural health inequalities may help in designing effective measures for improving population health.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Inequality of income between rural and urban households explains most of the malnutrition gap. 44 Understanding of the nature and the underlying factors behind urban-rural health inequalities may help in designing effective measures for improving population health. Present study reported that about 21.8% of the children were overweight and obese, it is much close to the global prevalence which has risen dramatically from just 4% in 1975 to over 18% in 2016.…”
Section: Discussionmentioning
confidence: 99%